Pengaruh Media Pembelajaran Berbasis Video Cerita Rakyat Nusantara Terhadap Pemahaman Nilai Moral Pada Siswa Kelas V SD Inpres Bangkala III Kota Makassar - Ningrat, Ismu; Satriawati; Firmansah Koesyono Efendi; Baharuddin Hafid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of learning media based on Nusantara folk tale videos on students' understanding of moral values in Grade V at SD Inpres Bangkala III in Makassar city. This study is motivated by the low understanding of moral values among students in Indonesian language learning, particularly in the material of Nusantara folk tales, which is caused by the use of conventional learning methods and the lack of utilization of engaging media .This research uses a quantitative approach with a type of pre-experimental research with the form of One-Group Pretest-Posttest Design. The population in this study is Grade V students at SD Inpres Bangkala III in Makassar City, totaling 65 students. The research sample consists of Grade V A students totaling 33 students, consisting of 18 male students and 15 female students, selected using purposive sampling technique. Data collection techniques were carried out through tests, observations, and documentation. Data analysis was conducted using descriptive and inferential analysis through normality tests, homogeneity tests, linearity tests, and hypothesis testing using paired samples tests with the assistance of SPSS software. The results of the study indicate that learning media based on Nusantara folk tale videos have a positive and significant effect on improving students' understanding of moral values in Indonesian language learning. This is proven through the comparison of pretest and posttest scores as well as the results of hypothesis testing. The average pretest score was 55.15, which falls into the poor category, while the average posttest score was 84.09, which falls into the good to very good category. The hypothesis test results showed a significance value (Sig.) of 0.001 < 0.05. Since the significance value is less than 0.05 (0.001 < 0.05), H₁ is accepted and H₀ is rejected. These results prove that there is a significant effect of Nusantara folk story-based video learning media on the understanding of moral values in fifth-grade students of SD Inpres Bangkala III, Makassar City. Thus, Nusantara folk story-based video learning media is declared effective in improving the understanding of moral values in fifth-grade students of SD Inpres Bangkala III, Makassar City.